2024 update of the AGIHO guideline on diagnosis and empirical treatment of fever of unknown origin (FUO) in adult neutropenic patients with solid tumours and hematological malignancies - Sandherr, Michael; Stemler, Jannik; Schalk, Enrico; Hattenhauer, Tessa; Hentrich, Marcus; Hertenstein, Bernd; Hohmann, Christian; Mellinghoff, Sibylle Christiane; Mispelbaum, Rebekka; Rieger, Christina; Schmidt-Hieber, Martin; Sprute, Rosanne; et al. (The lancet. Regional health, 2025)
Febrile Neutropenia is an emergency in the treatment of cancer patients. It requires prompt and evidence-based clinical and antimicrobial management. The implementation of standard operating procedures (SOP) across hospitals and outpatient cancer departments can improve the outcome of FN patients by reducing FN-related morbidity and mortality and by the continuation of cancer treatment. This guideline describes an evidence-based approach to risk stratification, epidemiology, diagnosis, and treatment. It is provided by the Infectious Diseases Working Party (AGIHO) of the German Society of Hematology and Medical Oncology (DGHO) and is an update of the 2017 version. Emerging aspects in epidemiology, diagnostic procedures, risk stratification, first-line antimicrobial treatment, empiric antifungal treatment and the duration of antimicrobial treatment are discussed and rated on evidence-based strength of recommendation and quality of evidence as described by the European Society of Clinical Microbiology and Infectious Diseases (ESCMID). By this, the aim of this guideline is to provide evidence-based recommendations on the management of febrile neutropenia in cancer patients for the practicing clinician.